Tailoring the Mechanistic Pathways and Kinetics of Decomposition of CH3CH2C(O)OCH2CH2O Radical: A DFT Study - Tayum, Nabam; Gour, Nand Kishor; Murugan, Arumugam; Mishra, Bhupesh Kumar (Asian Journal of Chemistry, 2023)
The potential energy surface (PES) of the oxidative pathways and unimolecular decomposition of CH3CH2C(O)OCH2CH2O radical formed from ethyl propionate has been investigated in details using ab initio density functional method. In present study, it is revealed that five major decomposition pathways with their kinetic and thermodynamics parameters. The geometries of reactants, transition states and product radicals were optimized using the model DFT method M06-2X along with the 6-31+G(d,p) basis set. The mechanistic, kinetic and thermochemical analysis was carried out at the M06-2X/aug-cc-pVTZ//M06-2X/6-311++G(d,p) level. Based on present results, it can be concluded that the oxidative pathway is the most significant for decomposition of CH3CH2C(O)OCH2CH2O radical. The rate coefficients for each reaction channels were determined in a wide range of temperature 250-450 K.